The Impact Of Leadership, Training, And Work Commitment On Work Productivity Through Employee Career Development - Kustini Kustini; Denok Sunarsi; Imas Masriah (STEBIS Bina Mandiri, 2026)
This research aims to analyze the influence of leadership, training, and work commitment on employee work productivity through career development. The research approach employs a quantitative method with Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis. The sample consists of 187 permanent employees. The results indicate that leadership, training, and work commitment have a significant positive effect on career development and work productivity. Career development also mediates the relationship between the independent variables and productivity. The R² values ​​show that the model explains 90.7% of the variation in career development and 93.8% of the variation in productivity.